2012
DOI: 10.1093/dnares/dsr045
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Mycoplasma hyopneumoniae Promoters: Sequence Definition and Genomic Distribution

Abstract: Several Mycoplasma species have had their genome completely sequenced, including four strains of the swine pathogen Mycoplasma hyopneumoniae. Nevertheless, little is known about the nucleotide sequences that control transcriptional initiation in these microorganisms. Therefore, with the objective of investigating the promoter sequences of M. hyopneumoniae, 23 transcriptional start sites (TSSs) of distinct genes were mapped. A pattern that resembles the σ70 promoter −10 element was found upstream of the TSSs. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…Our oriC system allowed us to assess the function of putative M. hyopneumoniae promoter sequences, and confirmed the identity of two promoter sequences that were active in controlling tetM expression. The P97 promoter sequence was recently predicted and we have verified that this is functional in our plasmid system [26]. Using the criteria identified by Weber Sde et al [26], we also predicted the location of the ldh promoter, and again demonstrated its activity in our plasmid system.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our oriC system allowed us to assess the function of putative M. hyopneumoniae promoter sequences, and confirmed the identity of two promoter sequences that were active in controlling tetM expression. The P97 promoter sequence was recently predicted and we have verified that this is functional in our plasmid system [26]. Using the criteria identified by Weber Sde et al [26], we also predicted the location of the ldh promoter, and again demonstrated its activity in our plasmid system.…”
Section: Discussionsupporting
confidence: 74%
“…However, other mycoplasmas may require an alternative promoter sequence, such as the spiralin gene promoter of Spiroplasma citri that has be shown to be active in several mycoplasma species [11,13,14]. In addition to constructing pMHO-2 utilising tetM and the spiralin gene promoter sequence, we produced plasmids pMHO-3 and pMHO-4 containing tetM with the putative promoter regions of the M. hyopneumoniae strain 232 P97 ciliary adhesin gene [26] and lactate dehydrogenase ( ldh ) gene respectively. In addition to altering the promoter sequences controlling tetM expression, we sought to determine whether or not a lower concentration of tetracycline would enhance the growth of transformants.…”
Section: Resultsmentioning
confidence: 99%
“…hyopneumoniae strain 7448 were classified according to the cis-elements found in the upstream region of the respective start codon. Analyses of all genes revealed that 429 of them (59%) had putative promoter sequences (according to Weber et al [12]) or repetitive element (present analysis) in the 5’ upstream region. Among these 429 genes, the most representative element in the 5’ upstream region were palindromic repeats plus promoter sequences (40%), followed by individual palindromic repeats (28%) and the combination of all putative sequences (tandem, palindromic and promoter) representing 16% (Fig 4A).…”
Section: Resultsmentioning
confidence: 63%
“…Identification of transcription start site (TSS) was performed for 23 genes of M . hyopneumoniae strain 7448 [12]. The analysis of these 23 genes in relation to the presence of DNA repeats revealed that 15 of them have at least one repetitive element located in the 5’ UTR region (S7 Table).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation